John Quincy Adams and American Global Empire. - Weeks, William Earl, 1957- (The University Press of Kentucky, 1992)
This is the story of a man, a treaty, and a nation. The man was John Quincy Adams, regarded by most historians as America's greatest secretary of state. The treaty was the Transcontinental Treaty of 1819, of which Adams was the architect. It acquired Florida for the young United States, secured a western boundary extending to the Pacific, and bolstered the nation's position internationally. As William Weeks persuasively argues, the document also represented the first determined step in the creation of an American global empire. Weeks follows the course of the often labyrinthine negotiations by.